Membrane contact sites—an interesting species, an interesting mix. (5th April 2013) - Miller, Victoria J; Stephens, David J
Abstract : In this issue of EMBO reports, Loewen and colleagues reveal a role for plasma membrane–endoplasmic reticulum contact sites in regulating phosphatidylcholine synthesis in budding yeast.